The Role of Social Media Influencers in Public Health Communication: Case COVID-19 Pandemic. Issue 3 (27th May 2022) - Pöyry, Essi; Reinikainen, Hanna; Luoma-Aho, Vilma
ABSTRACT: During public health crises, public organizations face a variety of strategic communication challenges, and the outbreak of the COVID-19 pandemic in 2020 is an extreme example. In Finland, the Prime Minister's Office initiated a communication campaign that utilized social media influencers to communicate timely instructions regarding the pandemic. However, it is uncertain how social media influencers adapt to briefings of public organizations given that they typically work with brands that align with their own interests and expertise, which rarely is epidemiology. We use the two-step flow of communication model and social influence theory to analyze research data that consisted of 96 Instagram posts, 108 Instagram Stories and 1097 comments. Qualitative content analysis was used to see how the influencers communicated about the pandemic and how their followers reacted. The results suggest that the influencers tried to adapt the messages to their own style, and, instead of committing to the wordings of the campaign, they shared general guidelines and, with their own example, showed how to behave during the pandemic. Their participation in the campaign helped affect social norms during the time of the crisis, which in the case of public health communication is a substantial, strategic goal.